Multiple Reflective Cracks in Semirigid Base Asphalt Pavement under Traffic Load Using XFEM - Lei Guo; Jinchao Yue; Pan Guo; Xiaofeng Wang (Advances in Civil Engineering)
This paper built a three-dimensional layered structure model of semirigid base asphalt pavement with single and double transverse reflective cracks based on the Extended Finite Element Method and fatigue fracture theory. The effects of the number of cracks, crack spacing, and crack length on the stress intensity factors (KI, KII, and Keff) under moving vehicle loads were studied. The fracture life of the asphalt pavement structure was calculated based on the Pairs formula. The results demonstrate that reflective cracks in semirigid asphalt pavement are composite cracks of type I and type II under moving vehicle loads, and shear fracture is the main reason for the failure of the base. The damage to the pavement base will be accelerated with the increase in the number of cracks and the length of the cracks. As the distance between the two reflection fractures is closer, the interaction between the cracks has a superimposed enhancement effect on the crack propagation. Compared with the single nonpenetrating crack model, the fatigue life of the nonpenetrating reflective crack in the double crack pavement structure with a crack spacing of 30 cm is reduced by 46.87%. The research on the propagation mechanism of reflective cracks in this paper provides the essential theoretical and numerical basis for the design, construction, working condition evaluation, and maintenance of pavement structures.